Cobalt-doped magnesium oxide pressure-transmitting medium for high pressure and high-temperature apparatus. Issue 4 (2nd October 2018) - Wu, Jingjun; Liu, Fangming; Zhang, Jiawei; Wang, Qiang; Liu, Yinjuan; Liu, Jin; Liu, Ke; He, Duanwei
ABSTRACT: Magnesium oxide (MgO) doped with cobalt (Co) semi-sintered pressure-transmitting medium (MCOPM) was prepared at 1200°C in air, starting with a pre-compressed mixture of MgO and cobalt oxide (CoO). The samples were characterized using powder X-ray diffraction, scanning electron microscopy, and thermal conductivity measurements. The results demonstrate that during the sintering process, the exchange of metal ions between the mixture powders introduced lattice defects into the MgO lattice structure, and an MgO–CoO solid solution was formed. Compared to commercial semi-sintered MgO pressure-transmitting medium (SSMPM), the temperature-generation efficiency of MCOPM-17 (MgO + 17 mol% CoO) improved by about 220% at the high pressure of 12 GPa with a cell assembly in a two-stage multi-anvil large volume press. Moreover, the thermal conductivity of CoO-doped MgO decreased with increasing CoO doping.